AFFECTING FACTORS TRANS LAND FUNCTION IN BALI - Sudemen, I Wayan; Darma, Ketut (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 1, Februari 2022 (pp.1-161), 2022)
Agricultural land conversion is one of the phenomena of changing agricultural land become non-agricultural as a result of development carried out by the government, private and public that alone. Destination in study this is identify factors that influence land use change in Province Bali. This study uses a quantitative approach using analytical tools panel data regression which is a combination of time series or time series data and cross section data. The results showed that The occurrence of conversion of paddy fields in regencies/cities in Bali Province is influenced by by total population, GDP per Capita and share Agriculture to GRDP. It turns out development total population whose influence significant with level real 95% (? = 5%), moderate which other non-significant .